Developing an Islamic psychospiritual module to promote posttraumatic growth among Muslim humanitarian workers in the Philippines: a study protocol - Basman, Anna Tajminah; Sidek, Suriati (Asian Scholars Network, 2024)
Muslim humanitarian workers often experience trauma due to the nature of their work, and there is a paucity of intervention programs available to promote positive transformation and posttraumatic growth (PTG). To address this gap, a study protocol was proposed based on literature reviews and subject matter interviews that identify the Islamic psychospiritual factors that promote PTG using the Analyse, Design, Develop, Implement and Evaluate (ADDIE) model. The study will implement a five-day workshop as a potential approach to promote PTG in a quasi-experimental study. A mixed methods ANOVA will be used to analyze results obtained from 108 participants, with 54 in the experimental group and 54 in the control group. The results of the study will show the potential changes in PTG scores, measured by Tedeschi and Calhoun's Posttraumatic Growth Inventory (PTGI), at two time points (pre-and post-intervention).